Taxation of Asset Securitization in Poland - Biernacki, Krzysztof (Opodatkowanie sekurytyzacji aktywów w Polsce, 2010)
Taxation of securitization in Poland mirrors the existing tax barriers related to the implementation of new financial services. Amendment of tax regulations with respect to one group of initiators - banks in Poland, shows how far-reaching the final influence of tax-related changes on profitability of the transaction may be. As a result of limiting that instrument exclusively to bank assets, the securitization market based on other assets or on transactions concluded with an SPV being an entity other than investment funds is, as a matter of fact, marginalized. Concluding, it should be pointed out that the final model of securitization in Poland has been shaped exclusively by the tax regulations. Such a situation may be perceived as a breach of competition rules, whereas it hinders the development of new securitization market segments.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 138, s. 9-16
Keywords: securization; taxation; bank assets